2012
DOI: 10.1088/0004-637x/756/1/96
|View full text |Cite
|
Sign up to set email alerts
|

SUBMILLIMETER FOLLOW-UP OFWISE-SELECTED HYPERLUMINOUS GALAXIES

Abstract: We have used the Caltech Submillimeter Observatory (CSO) to follow-up a sample of WISE-selected, hyperluminous galaxies, so called W1W2-dropout galaxies. This is a rare (∼ 1000 all-sky) population of galaxies at high redshift (peaks at z=2-3), that are faint or undetected by WISE at 3.4 and 4.6 µm, yet are clearly detected at 12 and 22 µm. The optical spectra of most of these galaxies show significant AGN activity. We observed 14 high-redshift (z > 1.7)W1W2-dropout galaxies with SHARC-II at 350 to 850 µm, with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
319
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(350 citation statements)
references
References 77 publications
28
319
3
Order By: Relevance
“…At present, our 13 photometric data points prevent us from disentangling the true nature of the reddened quasar SEDs, which are more complicated than a two-component model can describe. These objects are in the company of other newly discovered, complicated systems that are not yet fully understood and not well matched to any known SEDs, e.g., the "hot DOGs" in Wu et al (2012) or the dust-rich quasars in Dai et al (2012). Glikman et al (2007Glikman et al ( , 2012 identified several quasars whose flux variability between the epochs of their optical and near-infrared observations mimicked reddening, but which, upon spectroscopic observations, revealed a normal blue quasar.…”
Section: The Effect Of a Host Galaxy Component To The Reddening Fitsmentioning
confidence: 96%
“…At present, our 13 photometric data points prevent us from disentangling the true nature of the reddened quasar SEDs, which are more complicated than a two-component model can describe. These objects are in the company of other newly discovered, complicated systems that are not yet fully understood and not well matched to any known SEDs, e.g., the "hot DOGs" in Wu et al (2012) or the dust-rich quasars in Dai et al (2012). Glikman et al (2007Glikman et al ( , 2012 identified several quasars whose flux variability between the epochs of their optical and near-infrared observations mimicked reddening, but which, upon spectroscopic observations, revealed a normal blue quasar.…”
Section: The Effect Of a Host Galaxy Component To The Reddening Fitsmentioning
confidence: 96%
“…More recently, R W 4 -, where W4 is the WISE flux at 22 μm, used in conjunction with nondetections in the WISE W1 (3.4 μm) and W2 bands (see Eisenhardt et al 2012;Wu et al 2012, andStern et al 2014 for a discussion of W W 1 2 -dropout sources), have been shown to identify extremely reddened Type 1 quasars (Yan et al 2013;Ross et al 2014), though such objects are rare and have a low space density. Additionally, infrared-only colors, such as Spitzer IRAC color selection Stern et al 2005;Donley et al 2012) and WISE W W 1 2 -color selection (Stern et al 2012;Assef et al 2013), have been adopted to identify both unobscured and obscured AGNs, including Type 2 AGNs locally and at highredshift and highluminosity (e.g., Lacy et al 2015), though these color selections work best at brighter fluxes since star-forming galaxy contamination becomes significant at fainter fluxes (Barmby et al 2006;Cardamone et al 2008;Donley et al 2008;Mateos 2012;Mendez et al 2013).…”
Section: Selecting Reddened Broad-lined Agnsmentioning
confidence: 99%
“…Since they likely represent a short-lived crucial phase in the evolution of the most powerful AGN in the universe, probing the nuclear properties of such recently-discovered extreme objects can clearly benefit our understanding of overall AGN-galaxy co-evolution. This is our aim and here we report the first X-ray spectrum of a Hot DOG (namely WISE J183533.71+435549.1, hereafter W1835+4355, at z = 2.298, e.g., Wu et al 2012) obtained by XMM-Newton. Throughout this Letter we assume H 0 = 70 km s −1 Mpc −1 , Ω Λ = 0.73, and Ω M = 0.27.…”
Section: Introductionmentioning
confidence: 98%